Pengaruh Keahlian Dan Pengalaman Auditor Terhadap Audit Judgment - Andi Pattiware; husnayaini (LPPM STIEM, 2024)
his study aims to determine the effect of the expertise and experience of auditors at public accounting firms in the city of Makassar. Data collection techniques used primary data obtained from questionnaires. the population in this study were 34 auditors who worked in 5 public accounting firms in Makassar. The sampling technique in this study used the saturated sample technique. The results of the questionnaire data have been tested by instruments in the form of validity and reliability tests. Classical assumption test in the form of normality test, multicollinearity test, and heteroscedasticity test. Methods of data analysis using multiple linear regression analysis method.The results showed that the expertise and experience of the auditor simultaneously had a significant effect on audit judgment, the expertise of the auditor partially had a significant positive effect on audit judgment, and the experience of the auditor partially had a significant positive effect on audit judgment at a public accounting firm in Makassar.